Assessment of Stem Cross-Section Shape and Diameter at Breast Height of Eucalyptus Trees using Terrestrial LiDAR Data - da Silva, Matheus F. [UNESP]; dos Santos, Renato C. [UNESP]; Tommaselli, Antonio M.G. [UNESP]; Galo, Mauricio [UNESP] (My University, 2023)
LiDAR data offer new possibilities for obtaining geometric parameters of forest areas, such as diameter at breast height (DBH), basal area, height, volume, biomass, and carbon stock. In this context, Terrestrial Laser Scanners (TLS) are highly accurate and can be used to obtain the shape of tree trunks. In this study, the relationship between the circular model and the cross-sectional shape of eucalyptus trees is investigated. Based on the proposed method, the DBH estimated from TLS data showed Root Mean Square Error (RMSE) of 1.3 cm, for trees with a cross-section considered circular. Although the generalization of the circular model to the entire plot is acceptable, the results showed that additional evaluations are needed for other more precise applications, such as volume estimation.